Modeling and Development of Hybrid Energy Harvester for Self-Powered Iot Applications - Tengku Mohd Nasir, Tengku Muhamad Fizri (2017)
The project presents the models of a vibration energy harvester consisting of a piezoelectric with mass damper and spring as well as electret-based electrostatic. To construct this energy harvester, a mathematical model for both energy harvester is developed followed by a simulation in MATLAB/Simulink. The simulation is based on the mathematical models. Next is designing the model prototype in Tinkercad. The prototype consists of piezoelectric material holder and electrostatic material holder. The electrostatic energy harvester holder consists of a resonator, and electret material holder while the prototype for the piezoelectric consists of a piezoelectric layer holder. The prototype is then fabricated. The electrostatic energy harvester consists of electret material and a copper PCB. The electret material used is silicon dioxide. The electret is charged using a corona charger to embed the electrostatic charge onto the electret material. The piezoelectric energy harvester consists of a piezoelectric layer (PPA-1001) and 6 NdFeB magnets as the tip mass. The prototype will then be connected to a power management circuit and tested on a vertical shaker to get the output voltage.